PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN SONGKET DI NAGARI PANDAI SIKEK KEC. X KOTO, KAB. TANAH DATAR - Hidayat, Riski; Silfeni, Silfeni; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
This research aims to know the influence of marketing mix toward purchasing decision at Nagari Pandai Sikek Kec.X Koto Kab. Tanah Datar. This research of two varibles i.e marketing mix and purchasing decision. Type of this research is quantitative descriptive with causal assosiatif method. The population in this research using the formula widiyanto (2008: 34) to population numbers unknown so obtained samples as many as 96 people. The technique of sampling with purposive sample. Analysis technique with a simple regression test. Based on the research that has been done then the obtained results : (1) the marketing mix is a good category (57.29%), (2) purchasing decisions are on either category (72.92%), (3)hypothesis test result of simple linear regression obtained f countdown with sig. 0,000 < 0,05, then the marketing mix variables can explain the purchasing decision significantlywith the R Square of 0,297 that is where there is the influence of marketing mix towards purchasing decision of 29% and 71 % more influenced by other factorsKeyword: marketing mix, purchasing decisions